1988
DOI: 10.1302/0301-620x.70b2.3346298
|View full text |Cite
|
Sign up to set email alerts
|

Computerised tomographic assessment of the subtalar joint in calcaneal fractures

Abstract: Thirty-six patients with 39 fresh fractures of the calcaneus were investigated by standard radiography and by computerised tomography. It was found that the size and disposition of the fracture fragments and the degree of involvement of the posterior facet of the subtalarjoint were more clearly shown by CT scanning. We recommend this technique for assessment and particularly for pre-operative planning. Fig. 1 Diagram of the position of the ankle and foot in the CT scanner;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In our centre, we tend to treat the calcaneal fractures nonoperatively with a below knee cast. We do not routinely request for Computer Tomography Scan 6,7 . For this study, we used the Essex-Lopresti classification 2 , which is based on the plain radiographs of the calcaneum.…”
Section: Discussionmentioning
confidence: 99%
“…In our centre, we tend to treat the calcaneal fractures nonoperatively with a below knee cast. We do not routinely request for Computer Tomography Scan 6,7 . For this study, we used the Essex-Lopresti classification 2 , which is based on the plain radiographs of the calcaneum.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography is essential for preoperative evaluation of intra-articular calcaneal tractures.l'' [7][8][9][10][12][13][14][15][16][17][18][19] Coronal CT images help evaluate superior posterior facet disruption, sustentaculum tali depression, peroneal or flexor hallucis tendon entrapment, and widening and loss of calcaneal height. Axial CT images show disruption of the inferior part of the posterior facet, calcaneocuboid joint involvement, and widening of the calcaneus."…”
Section: Discussionmentioning
confidence: 99%
“…The subtalar joint, because of its complexity, has historically been difficult to assess both clinically and radiographically. This is demonstrated by the numerous studies that have been dedicated to clinical evaluation, 5,6,8,20,21 kinetic evaluation, 24,25,28,29,31,32,37 and radiography 2,4,9,11,14,17,22,27,33 of the subtalar joint.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have indicated that computed tomography (CT) is superior in assessing both normal and pathologic conditions of the subtalar joint. 4,11,17,27,33,36 It is the authors' understanding that there has been little work with CT when looking at subtalar motion. CT has superior ability to diagnose subtle fractures 4,11 and arthritis, 27 and we believe that it may be useful to help in understanding subtalar motion as well.…”
Section: Introductionmentioning
confidence: 99%